Adding Hydrogen to the Fuel-Air Mixture in Engines - Nasirov Ilham Zakirovich; Rakhmonov Khurshidbek Nurmuhammad ugli; Abbasov Saidolimkhon Jaloliddin coals (Genius Journals, 2022)
Adding 5% hydrogen to a conventional gasoline-air mixture in a gasoline engine reduced the effective fuel consumption by 14% and the amount of unburned hydrocarbons in the exhaust gases by 2-3 times, and carbon monoxide by 0.1%. The addition of hydrogen increased the octane number of gasolines to 8-10 units and completely eliminated the use of tetraethyl lead added to them
Keywords: Hydrogen; internal combustion engine; exhaust gases; environment